Levels Of Depression Among Wives Of Alcoholics And Non- Alcoholics- A Comparative Study - G.S. Sumathi (Indian Journal of Psychiatric Nursing)
Introduction: Alcohol use affects each member of the family - from the unborn child to the alcoholic's spouse. The spouse may have feelings of hatred, self-pity, avoidance of social contacts, may suffer exhaustion and become physically or mentally ill. Aim: Present study aimed to assess and compare the levels of depression among wives of alcoholics and non–alcoholics. Material and method: The sample comprised of 60 wives of alcoholics and 60 wives of non - alcoholics who were selected purposely. The tools used in study were structured interview schedule and 21 items Beck Depression Inventory. Results: The findings of the study revealed that exactly 50% of wives of alcohol dependents had severe level of depression and 35 % had moderate level of depression whereas 33.7% and 63.7% of wives of non-alcoholics had mild and minimal level of depression respectively. It also showed a significant association between the levels of depression and selected demographic variables such as duration of alcohol intake, reasons for alcohol intake and amount spent in buying alcohol at p<0.01. Conclusion: Study recommends the proper consultation and health services for wives of alcoholics.